Meningkatan Minat Belajar Melalui Model Reciprocal Teaching pada Murid Kelas V SD Inpres Antang 1 Kota Makassar - Abdul Wahid; Nur Afni (STKIP Andi Matappa Pangkep, 2022)
This study examines Increasing Interest in Learning through the Reciprocal Teaching Model in Class V Students of SD Inpres Antang 1 Kota Makassar. The main problems in the research are; How to increase interest in learning through the Reciprocal Teaching model in fifth grade students at SD Inpres Antang 1, Makassar Regency. The main objective of this research is to increase students' interest in learning and apply the Reciprocal Teaching model to increase learning interest in fifth grade students of SD Inpres Antang 1, Makassar Regency. This research uses classroom action research. The research subjects were fifth grade students at SD Inpres Antang 1 which consisted of 10 boys and 14 girls. The data collection procedure used observation, student learning interest questionnaires, and documentation. Data analysis used descriptive analysis. The results showed that the student's interest in learning in the first cycle with the percentage of classical student interest in learning was 58.3% and there was an increase in learning interest in the second cycle with the percentage of classical student interest in learning 83.3%, so there was an increase in student interest in learning from cycle I to cycle II.